Hors du mariage, point de salut ? Regards de réformateurs et de féministes (Allemagne, fin xixe – début xxe siècles) - Anne-Laure Briatte-Peters (Genre & Histoire)
Starting from the central position of wedlock in bourgeois women’s lives in the 19th century, the article analyses how the perception of women without husbands changed progressively within the German bourgeoisie over the long 19th century. The first section considers the rising awareness of the problem of women without husbands, who are frequently represented in stereotypical fashion. Secondly, the article shows how women explored alternative ways of living outside of matrimony and tried in vain to reform family law at the moment of the unification of German civil code. The final section analyses the public debate on matrimony and alternative conceptions of love and sexuality, which contributed to an emerging social acceptance of women without husbands on the eve of the First World War.